ON THE RELATIONSHIP BETWEEN THE MIND DEVELOPMENT AND MENTAL EDUCATION - Buhriy, O.V. (Pedagogy of Higher and Secondary Education, 2022)
The essence o f the notions: “mental development” and “mental education ” are revealed in the article. Educational abilities o f the process o f studies in modern school are shown.